MISIUNEA BISERICII ȘI FENOMENUL RELAȚIILOR SOCIALE INSTRUMENTALE ÎN ROMÂNIA POSTCOMUNISTĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Mission of the Church and the Phenomenon of Instrumental Social Relations in Post-Communist RomaniaPsychological and sociological investigations, as well as philosophical reflections on the harmful influences of communism point to the fact that the area of public life most seriously affected by Communism is the social solidarity of the Romanian people. In spite of the transformations that Romania has experienced in the past century, some informal practices and institutions have survived and adapted, and continue to influence Romanian society at the present time. Such practice is the use of instrumental social relationships, also called utility relationships. In the present study we will show that the Church, by virtue of its nature and mission, possesses the most effective means to counteract the instrumental component of social relationships. Despite the confessional diversity that characterizes it, the Church holds in its nature and mission the code of the social normality of a community or nation.